QUALITATIVE STUDY : COPING OF THE MOTHERS AFTER SPONTANEOUS ABORTIONS - Dwy Kartika, Enthyn Anaway Bintang; Pratiwi, Cesa Septiana; Mamnu’ah, Mamnu’ah (Universitas Aisyah Pringsewu, 2023)
Background: The incidence of spontaneous abortion reaches 226 people per 100,000 live births. Mothers with a history of spontaneous abortion have short- to long-term psychological vulnerabilities and comorbidities. Psychological disorders can persist for up to 1 year after spontaneous abortion and can affect the social impact on the affected mother. Objective: This study aimed to explore in depth the coping of spontaneous post-abortion womens. Method: This qualitative research uses a phenomenological approach. Participants were taken using Purposive Sampling technique with 8 mothers who had a history of spontaneous abortion for a maximum of 3 months and were recorded as patients at Pratama Gemilang Medika Piyungan Bantul Clinic Yogyakarta. In this study, data analysis uses Thematic analysis. Result: Formed in 8 main themes, namely physical (total rest at home), accepting (determined to heal), spiritual (surrendering to God and sincere, listening to tausiah in the surrounding environment, listening to da'wah through social media, praying a lot and strengthening prayers and increasing Quran reading), refreshing (walking with husband), distraction (busying yourself), hobby (me time or healing), positive thinking and preparing carefully for the next pregnancy program. The theme has been identified in reference to a general purpose. Conclusion: The coping strategy chosen for each post-abortion mother is adjusted to the emotional condition experienced, chosen by herself without interference from other parties, by letting the post-abortion mother determine which strategy is more appropriate and can make her take a positive meaning of the situation she is experiencing. It is hoped that there will be Continuity Of Care (COC) and spiritual support provided by midwives as health workers, especially to spontaneous abortion mothers.